Aerobic exercise training‐induced follistatin‐like 1 secretion in the skeletal muscle is related to arterial stiffness via arterial NO production in obese rats. Issue 10 (18th May 2022) - Inoue, Kenichiro; Fujie, Shumpei; Horii, Naoki; Yamazaki, Henry; Uchida, Masataka; Iemitsu, Motoyuki
Abstract: Follistatin‐like 1 (FSTL1), which is mainly secreted from skeletal muscle and myocardium, upregulates protein kinase B (Akt) and endothelial nitric oxide synthase (eNOS) phosphorylation in vascular endothelial cells. It is unclear whether skeletal muscle‐ and myocardium‐derived FSTL1 secretion induced by aerobic exercise training is involved in the reduction of arterial stiffness via arterial NO production in obese rats. This study aimed to clarify whether aerobic exercise training‐induced FSTL1 secretion in myocardium and skeletal muscle is associated with a reduction in arterial stiffness via arterial Akt‐eNOS signaling pathway in obese rats. Sixteen Otsuka Long‐Evans Tokushima Fatty (OLETF) obese rats were randomly divided into two groups: sedentary control (OLETF‐CON) and eight‐week aerobic exercise training (treadmill for 60min at 25m/min, 5days/week, OLETF‐AT). Eight Long‐Evans Tokushima Otsuka (LETO) rats were used as a healthy sedentary control group. In OLETF‐CON, serum FSTL1, arterial Akt and eNOS phosphorylation, and arterial nitrite/nitrate (NOx) levels were significantly lower, and carotid‐femoral pulse wave velocity (cfPWV) was significantly greater than those in LETO. These parameters were improved in the OLETF‐AT compared to the OLETF‐CON. In the OLETF‐AT, FSTL1 levels in slow‐twitch fiber‐rich soleus muscle were significantly greater than those in the OLETF‐CON, but not in myocardium, fast‐twitch fiber‐rich tibialis anterior muscle, and adipose tissue. Serum FSTL1 levels were positively correlated with soleus FSTL1, arterial eNOS phosphorylation, and NOx levels and negatively correlated with cfPWV. Thus, aerobic exercise training‐induced FSTL1 secretion in slow‐twitch fiber‐rich muscles may be associated with a reduction in arterial stiffness via arterial NO production in obese rats. Abstract : In obese rats, aerobic exercise training increased FSTL1 levels in slow‐twitch fiber‐rich soleus muscle and serum but not in myocardium, fast‐twitch fiber‐rich tibialis anterior muscle, and adipose tissue. Serum FSTL1 levels were positively correlated with soleus FSTL1, arterial eNOS phosphorylation levels, and arterial NOx production and were negatively correlated with cfPWV. Our findings suggest that aerobic exercise training‐induced FSTL1 secretion in slow‐twitch fiber‐rich muscle may be associated with a reduction in arterial stiffness via arterial NO production in obese rats.